Hubungan dan Prevalensi Tingkat Depresi, Tingkat Kecemasan, dan Tingkat Stres dengan Irritable Bowel Syndrome Pada Siswa/I SMAN 1 Lenek Kabupaten Lombok Timur - Hamdi, Zainul; Prajitno, Sugianto; Azmi, Fahriana; Suanjaya, Made Agus (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Irritable bowel syndrome (IBS) is a chronic and recurrent functional intestinal disorder, in the form of abdominal pain or discomfort and defecation pattern disorders that occur 1 time per week for at least 3 months, without any underlying structural abnormalities. Irritable bowel syndrome is a multifactoral disease that has several pathogenesis. Psychological factors such as stress, anxiety and depression can strongly affect the work of the colon. The colon has many neurons associated with the cerebrum. Part of the colon is controlled by the CNS, which responds to stress. This study aims to determine the prevalence of stress, anxiety, depression and the incidence of irritable bowel syndrome, as well as determine the relationship between stress, anxiety, depression and the incidence of irritable bowel syndrome in students of SMA N 1 Lenek East Lombok Regency. Analytical quantitative research with cross sectional research design. The sampling technique uses stratified random sampling. The research was conducted at SMA N 1 Lenek, East Lombok Regency. The study sample was 96 people. The data obtained were analyzed by the Chi-Square correlation test. The prevalence of irritable bowel syndrome in respondents was 40 people (41.7%), the prevalence of normal stress levels in respondents amounted to 36 people (37.5%), the prevalence of normal anxiety levels in respondents amounted to 17 people (17.7%), the prevalence of normal depression levels in respondents amounted to 45 people (46.9%). There is a significant relationship between stress and the incidence of irritable bowel syndrome. The p-value is 0.005 (p-value < 0.05). There was no significant association between anxiety and the incidence of irritable bowel syndrome. The p-value is 0.153 (p-value > 0.05). There is a significant relationship between depression and the incidence of irritable bowel syndrome. The p-value is 0.014 (p-value < 0.05). Conclusion: There is a relationship between stress and depression with the incidence of irritable bowel syndrome, but there is no relationship between anxiety and the incidence of irritable bowel syndrome in students of SMA N 1 Lenek East Lombok Regency. Keywords: Irritable Bowel Syndrome, Stress, Anxiety, DepressionABSTRAK Irritable bowel syndrome (IBS) adalah gangguan intestinal fungsional kronis dan berulang, berupa nyeri atau rasa tidak nyaman pada abdomen serta gangguan pola defekasi yang terjadi 1 kali per minggu setidaknya 3 bulan, tanpa adanya kelainan struktural yang mendasarinya. Irritable bowel syndrome merupakan penyakit multifaktoral yang memiliki beberapa patogenesis. Faktor psikologis seperti stres, kecemasan dan depresi dapat secara kuat memengaruhi kerja kolon. Kolon memiliki banyak neuron yang berhubungan dengan cerebrum. Sebagian kolon dikontrol oleh SSP, yang berespon terhadap stres. Penelitian ini bertujuan untuk mengetahui prevalensi stres, kecemasan, depresi dan kejadian irritable bowel syndrome, serta mengetahui hubungan stres, kecemasan, depresi dan kejadian irritable bowel syndrome pada siswa/i SMA N 1 Lenek Kabupaten Lombok Timur. Penelitian kuantitatif analitik dengan desain penelitian cross sectional. Teknik pengambilan sampel menggunakan stratified random sampling. Penelitian dilakukan di SMA N 1 Lenek Kabupaten Lombok Timur. Sampel penelitian sebanyak 96 orang. Data yang diperoleh dianalisis dengan uji korelasi Chi-Square. Prevalensi irritable bowel syndrome pada responden 40 orang (41,7%), prevalensi tingkat stres normal pada responden berjumlah 36 orang (37,5%), prevalensi tingkat kecemasan normal pada responden berjumlah 17 orang (17,7%), prevalensi tingkat depresi normal pada responden berjumlah 45 orang (46,9%). Terdapat hubungan yang signifikan antara stres dengan kejadian irritable bowel syndrome. Nilai p-value 0,005 (p-value < 0,05). Tidak terdapat hubungan yang signifikan antara kecemasan dengan kejadian irritable bowel syndrome. Nilai p-value 0,153 (p-value > 0,05). Terdapat hubungan yang signifikan antara depresi dengan kejadian irritable bowel syndrome. Nilai p-value 0,014 (p-value < 0,05). Terdapat hubungan antara stres dan depresi dengan kejadian irritable bowel syndrome, Namun tidak terdapat hubungan kecemasan dengan kejadian irritable bowel syndrome pada siswa/i SMA N 1 Lenek Kabupaten Lombok Timur. Kata Kunci: Irritable Bowel Syndrome, Stres, Kecemasan, Depresi